Inhibition of Partially Purified Xanthine Oxidase Activity from renal failure patients by Theophylline and Metronidazole - N.I. Al-Leheebe; O.Y. Al-Abbasy; I.S.AL-Flaeyh (Tikrit Journal of Pure Science)
Xanthine oxidase (XO) was  purified from sera of patients with renal failure by using ammonium sulfate and dialysis with a specific activities  2.1×10-3 and 5.6×10-3 unit/mg protein respectively. By using anion exchange chromatography techniques, One protein peak of  XO activity was obtained with specific activity 78×10-3unit/mg protein and with purification fold of 134.02 compared to crude enzyme. One isoenzyme was obtained having a molecular weight  of   255344  Dalton approximately.